2009
DOI: 10.1097/rli.0b013e3181a654a5
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double-Strand Breaks and Their Repair in Blood Lymphocytes of Patients Undergoing Angiographic Procedures

Abstract: gamma-H2AX immunofluorescence microscopy is a reliable and sensitive method for measuring the induction and repair of DNA damage caused by ionizing radiation during angiography. To estimate radiation doses delivered during procedures and to consider patients individual repair capacity, postangiography DSB-yields should be compared with DSB-yields after fractioned in vitro irradiation imitating examination conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…However, a separate consideration of the various examined bodily regions resulted in very good correlation coefficients (e. g. r = 0.71 for pelvis-leg angiography, r = 0.96 for abdominal angiography) Normalized to the individual dose-area product, significant differences were shown for the individual examination regions; the degree of damage was the highest for cardiac catheterization, followed by abdominal interventions, angiography of the pelvic-leg circulatory pathway and the cerebrum. These differences can be explained by the varying blood volumes of the different body regions and the associated various quantities of exposed lymphocytes [25,26]. One of these studies also demonstrated that chemotherapy itself induces DNA damage, thus distorting the actual radiation damage [25].…”
Section: Dsb After Angiographymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a separate consideration of the various examined bodily regions resulted in very good correlation coefficients (e. g. r = 0.71 for pelvis-leg angiography, r = 0.96 for abdominal angiography) Normalized to the individual dose-area product, significant differences were shown for the individual examination regions; the degree of damage was the highest for cardiac catheterization, followed by abdominal interventions, angiography of the pelvic-leg circulatory pathway and the cerebrum. These differences can be explained by the varying blood volumes of the different body regions and the associated various quantities of exposed lymphocytes [25,26]. One of these studies also demonstrated that chemotherapy itself induces DNA damage, thus distorting the actual radiation damage [25].…”
Section: Dsb After Angiographymentioning
confidence: 99%
“…These differences can be explained by the varying blood volumes of the different body regions and the associated various quantities of exposed lymphocytes [25,26]. One of these studies also demonstrated that chemotherapy itself induces DNA damage, thus distorting the actual radiation damage [25]. …”
mentioning
confidence: 99%
“…For example, gH2AX focus quantification has been used to assess the risk of exposure to ionizing radiation during clinical computed tomographic scans (59)(60)(61)(62) and to estimate the dose during radiotherapy (63)(64)(65) or in case of radiation accidents (66). Infrastructures for high-throughput biodensitometry screening after a radiologic event have been developed based on the gH2AX assay (67), and the European Biodosimetry Network is conducting large studies to evaluate the use of gH2AX focus quantification as a risk assessment tool in such cases (68).…”
Section: Reevaluation Of the Most Commonly Used Dsb Markermentioning
confidence: 99%
“…1 As the result of rapid technological evolution, the number of CT examinations is still rising, 2 even with the significant medical x-ray exposure 2,3 and the increasing awareness of the potential risks of even relatively low radiation doses 2,4 -especially in usage as a screening tool 5 or in serial use. 6 Biologic experiments have demonstrated that the number of DNA double-strand breaks is closely related to the applied dose.…”
mentioning
confidence: 99%
“…6 Biologic experiments have demonstrated that the number of DNA double-strand breaks is closely related to the applied dose. 3,7 Several techniques for CT dose reduction, maintaining image quality on a diagnostic level, became a hot topic in clinical research. [8][9][10][11] Automated attenuation-based tube current modulation or so-called automatic exposure control techniques are widely used.…”
mentioning
confidence: 99%